Financial risk protection of Thailand's universal health coverage: results from series of national household surveys between 1996 and 2015 - Viroj Tangcharoensathien; Kanjana Tisayaticom; Rapeepong Suphanchaimat; Vuthiphan Vongmongkol; Shaheda Viriyathorn; Supon Limwattananon (BMC, 2020)
Abstract Background Thailand, an upper-middle income country, has demonstrated exemplary outcomes of Universal Health Coverage (UHC). The country achieved full population coverage and a high level of financial risk protection since 2002, through implementing three public health insurance schemes. UHC has two explicit goals of improved access to health services and financial protection where use of these services does not create financial hardship. Prior studies in Thailand do not provide evidence of long-term UHC financial risk protection. This study assessed financial risk protection as measured by the incidence of catastrophic health spending and impoverishment in Thai households prior to and after UHC in 2002. Methods We used data from a 15-year series of annual national household socioeconomic surveys (SES) between 1996 and 2015, which were conducted by the National Statistic Office (NSO). The survey covered about 52,000 nationally representative households in each round. Descriptive statistics were used to assess the incidence of catastrophic payment as measured by the share of out-of-pocket payment (OOP) for health by households exceeding 10 and 25% of household total consumption expenditure, and the incidence of impoverishment as determined by the additional number of non-poor households falling below the national and international poverty lines after making health payments. Results Using the 10% threshold, the incidence of catastrophic spending dropped from 6.0% in 1996 to 2% in 2015. This incidence reduced more significantly when the 25% threshold was applied from 1.8 to 0.4% during the same period. The incidence of impoverishment against the national poverty line reduced considerably from 2.2% in 1996 to approximately 0.3% in 2015. When the international poverty line of US$ 3.1 per capita per day was applied, the incidence of impoverishment was 1.4 and 0.4% in 1996 and 2015 respectively; and when US$ 1.9 per day was applied, the incidence was negligibly low. Conclusion The significant decline in the incidence of catastrophic health spending and impoverishment was attributed to the deliberate design of Thailand's UHC, which provides a comprehensive benefits package and zero co-payment at point of services. The well-founded healthcare delivery system and favourable benefits package concertedly support the achievement of UHC goals of access and financial risk protection.